2021
DOI: 10.4067/s0718-58392021000200191
|View full text |Cite
|
Sign up to set email alerts
|

Effects of submergence stress at the vegetative growth stage on hybrid rice growth and grain yield in China

Abstract: Submergence stress can greatly limit grain yield of inbred rice (Oryza sativa L.), but the effects of submergence on hybrid rice are unclear. A pot experiment was conducted to clarify the effects of submergence that happens at the vegetative growth stage on two Chinese hybrid rice cultivars. The rice cultivars Zheyou-18, an indica-japonica hybrid, and Yliangyou-689, an indica hybrid, were planted under two treatments, submergence (43 cm depth of tap water for about 2 wk) and control (no submergence). Results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…This kind of information is valuable for buyers and processors as they can adjust their exporting volume or arrange other procurement channels to cover the loss when a decrease in production is predicted. This information is also helpful in policy making towards sustainable production for future years [57]. For example, the government or international organizations can monitor whether the coastal areas have been developed for aquaculture use illegally and if so, to what extent.…”
Section: Discussion On Monitoring Shrimp Ponds Using Rs Technologymentioning
confidence: 99%
“…This kind of information is valuable for buyers and processors as they can adjust their exporting volume or arrange other procurement channels to cover the loss when a decrease in production is predicted. This information is also helpful in policy making towards sustainable production for future years [57]. For example, the government or international organizations can monitor whether the coastal areas have been developed for aquaculture use illegally and if so, to what extent.…”
Section: Discussion On Monitoring Shrimp Ponds Using Rs Technologymentioning
confidence: 99%
“…Increased temperature significantly affects the growth and quality of rice varieties in India and the Himalayan region [36]. Sustained high temperatures reduce rice quality and grain weight [37]. The experiment analyzed the allocation of climate resources, production efficiency and comprehensive effects.…”
Section: Quantitative Evaluation Of the Allocation And Production Of ...mentioning
confidence: 99%
“…Flooding stress is a serious form of abiotic stress and it can cause yield losses (Table 1) of up to 70% [84]. However, yield losses largely depend on the stage of plant growth (Table 1) and the intensity of flooding stress [54,[85][86][87][88][89][90]. For instance, Ploschuk et al [91] reported that flooding stress at the vegetative growth stages in barley and canola caused more yield losses as compared to flooding stress at the reproductive stage.…”
Section: Crop Yieldmentioning
confidence: 99%